Digital Governance and Data Security: The Impact of IT Governance Maturity on Compliance, Fraud Prevention, and Investor Confidence - Sucipto, Rian (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
This study assesses the influence of IT governance maturity(ITGM) on compliance (COMPLY), fraud prevention (FRAUDP),and investor trust in data-intensive public companies acrosssectors. Using a firm-year panel design (±2019–2025), we constructan ITGM index based on auditable documentary evidence(structure & roles, policies & controls, risk management,compliance & audit, incident resilience, culture & training) and twomediator constructs—COMPLY and FRAUDP. Investor trust isproxied using cost of equity (COE), bid–ask spread, Tobin's Q/PBV,and analyst coverage. The relationships are tested through fixedeffectspanel regression (firm & year), mediation tests(bootstrap/SEM), and moderation by critical data intensity (CDI),with robustness tests (alternative proxies, index redefinition,winsorizing). The results show that ITGM has a positive effect onCOMPLY and FRAUDP, and both reduce COE and increasevaluation (Q/PBV)—confirming the dual mediation mechanism fromIT governance to investor confidence. Furthermore, the effect ofITGM is stronger in firms with high CDI, underscoring theimportance of data materiality. The findings remain consistentacross robust specifications. The study's contributions include theintegration of comprehensive and auditable maturity measures, theexploration of dual mediation paths that explain value channels,and the examination of materiality moderation to enhance therelevance of policies and practices. Practical implicationsrecommend strengthening IT governance structures, implementingmeasurable controls, and transparent, metrics-based disclosuresto build sustainable market confidence.